2017
DOI: 10.2527/jas2017.1665
|View full text |Cite
|
Sign up to set email alerts
|

Effects of rotating antibiotic and ionophore feed additives on volatile fatty acid production, potential for methane production, and microbial populations of steers consuming a moderate-forage diet

Abstract: Ionophores and antibiotics have been shown to decrease ruminal methanogenesis both in vitro and in vivo but have shown little evidence toward a sustainable means of mitigation. Feed additive rotation was proposed and investigated for methane, VFA, and microbial population response. In the present study, cannulated steers ( = 12) were fed a moderate-forage basal diet in a Calan gate facility for 13 wk. In addition to the basal diet, steers were randomly assigned to 1 of 6 treatments: 1) control, no additive; 2)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 45 publications
1
12
0
Order By: Relevance
“…Supporting our results, others have also reported increased concentration of rumen propionate and total VFA, and reduced concentration of rumen acetate and butyrate when narasin was fed to beef cattle (Miszura et al, 2018;Polizel et al, 2020). Also corroborating with this study, flavomycin (Mogentale et al, 2010;Crossland et al, 2017) or salinomycin (Olumeyan et al, 1986;Zinn, 1986) supplementation to beef cattle consuming or not a forage-based diets was not capable of changing ruminal fermentation parameters. In fact, Olumeyan et al (1986) and Zinn (1986) reported that rumen fermentation only changed when the diets had increased amount of grain.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…Supporting our results, others have also reported increased concentration of rumen propionate and total VFA, and reduced concentration of rumen acetate and butyrate when narasin was fed to beef cattle (Miszura et al, 2018;Polizel et al, 2020). Also corroborating with this study, flavomycin (Mogentale et al, 2010;Crossland et al, 2017) or salinomycin (Olumeyan et al, 1986;Zinn, 1986) supplementation to beef cattle consuming or not a forage-based diets was not capable of changing ruminal fermentation parameters. In fact, Olumeyan et al (1986) and Zinn (1986) reported that rumen fermentation only changed when the diets had increased amount of grain.…”
Section: Discussionsupporting
confidence: 91%
“…Supporting this statement, Bell et al (2017) and Polizel et al (2020) also reported similar rumen pH values of beef steers offered a high forage-based diets with monensin and narasin, respectively. Accordingly, Crossland et al (2017) did not observe any effect of flavomycin or monensin supplementation on rumen pH of beef steers offered a moderate forage-based diet. In fact, the ruminal pH in the present study was within a range that supports and maintains adequate fiber digestion in ruminants (Yokoyama and Johnson, 1988).…”
Section: Discussionmentioning
confidence: 67%
See 3 more Smart Citations